2009
DOI: 10.1063/1.3093383
|View full text |Cite
|
Sign up to set email alerts
|

The truncation model of the derivative nonlinear Schrödinger equation

Abstract: The derivative nonlinear Schrödinger (DNLS) equation is explored using a truncation model with three resonant traveling waves. In the conservative case, the system derives from a time-independent Hamiltonian function with only one degree of freedom and the solutions can be written using elliptic functions. In spite of its low dimensional order, the truncation model preserves some features from the DNLS equation. In particular, the modulational instability criterion fits with the existence of two hyperbolic fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Miranda et al 29 studied the nonlinear wave-wave interactions in space plasmas and reported the phenomenon of intermittent chaos. Chaos in a three-waves truncation model of the derivative NLSE for nonlinear Alfv en waves has been studied by Sanmartin et al 30 and Sanchez-Arriaga et al [31][32][33] Mori and Janssen 34 derived an expression relating the kurtosis of the sea surface elevation and the occurrence probability of freak waves generated via nonlinear four-wave modulational interactions. Their statistical theory is in good agreement with observational data of extreme wave events.…”
Section: Introductionmentioning
confidence: 98%
“…Miranda et al 29 studied the nonlinear wave-wave interactions in space plasmas and reported the phenomenon of intermittent chaos. Chaos in a three-waves truncation model of the derivative NLSE for nonlinear Alfv en waves has been studied by Sanmartin et al 30 and Sanchez-Arriaga et al [31][32][33] Mori and Janssen 34 derived an expression relating the kurtosis of the sea surface elevation and the occurrence probability of freak waves generated via nonlinear four-wave modulational interactions. Their statistical theory is in good agreement with observational data of extreme wave events.…”
Section: Introductionmentioning
confidence: 98%
“…Low-dimensional chaos of DNLS can also be studied by considering Alfvén modulational wave coupling processes (Sánchez-Arriaga et al, 2009;Miranda et al, 2012). Sánchez-Arriaga et al (2009) studied a truncation model of DNLS with three resonant traveling waves.…”
Section: Jatenco-pereira Et Al: Alfvén Waves In Dusty Plasmasmentioning
confidence: 99%
“…The aforementioned studies on Alfvén chaos elucidate how Alfvén intermittency appears in space and astrophysical plasmas, such as the magnetic intermittent turbulence observed in the solar wind (Koga et al, 2007;Sahraoui, 2008;Chian and Miranda, 2009;Chian and Muñoz, 2011), due to nonlinear dynamical phenomena such as the type-I intermittency induced by a saddle-node bifurcation, the crisisinduced intermittency induced by an interior crisis, and the extrinsic intermittency induced by a noise (Hada et al, 1990;Chian et al, 1998Chian et al, , 2006Chian et al, , 2007Rempel et al, 2006Rempel et al, , 2008Sánchez-Arriaga et al, 2009;Miranda et al, 2012).…”
Section: Jatenco-pereira Et Al: Alfvén Waves In Dusty Plasmasmentioning
confidence: 99%
“…Chaos in a three-wave truncation model of the derivative nonlinear Schrödinger equation for nonlinear Alfvén waves has been studied by Sanmartin et al 16 and Sánchez-Arriaga et al 17,18,19 . Mori and Janssen 20 derived an expression relating the kurtosis of the sea surface elevation and the occurrence probability of freak waves generated via nonlinear four-wave modulational interactions.…”
Section: Introductionmentioning
confidence: 99%